Alternative methods for egg-treatment using crucian carp (Carassius carassius L. 1758) modell - Sokoray-Varga Solt, Ferenc; Demény, Ferenc; Boczonádi, Zsolt; Urbányi, Béla; Müller, Tamás (Animal welfare, Ethology and Housing Systems (AWETH), 2010)
The most common disease of hatchery-reared fish is the aquatic fungi (Saprolegnia spp). The aim of our study was to control fungal infection on fish and fish eggs by applying four different herbal extracts (horseradish, thyme, nuts, lesser celandine) or salt solution. As no data were available in the scientific literature, we used concentrations that are commonly used in human medicine. In our experiment, the treatment was repeated twice a day or was used continuously, in which case three repetitions were applied during each treatment. According to the first step of the treatment, 150 Crucian Carp (Carassius carassius) eggs were placed in Petri dishes. Most of the eggs were inseminated, the rest ensured proper conditions for the aquatic fungi to evolve. The number of the infected eggs, the hatching and the early fry percent were observed. According to our results, we claim that all of the extracts had a clear effect on the number of infected eggs: the number of Saprolenga infection was observed significantly (Chi2, p < 0.05) less (20,79±9,39 %) in the treated group than in the control eggs. Considering the hatching and the early fry percent, the salt solution seemed to be more effective than the herb extracts. Moreover, some of the extracts had negative effects on the eggs: although the fungi did not evolve, the inseminated eggs did not hatch. Finally, thyme seemed to be the most effective extract. However the hatching and the early fry percent were far from the expected values, which might have resulted from the high tannic acid content of the extract.
Keywords: herbal extract; fish egg treatment; aquatic fungi; Saprolegnia spp.; herbal treatment